2013
DOI: 10.4161/pri.22851
|View full text |Cite
|
Sign up to set email alerts
|

The prion protein family

Abstract: Although the pivotal implication of the host-encoded Prion protein, PrP, in the neuropathology of transmissible spongiform encephalopathy is known for decades, its biological role remains mostly elusive. Genetic inactivation is one way to assess such issue but, so far, PrP-knockout mice did not help much. However, recent reports involving (1) further studies of these mice during embryogenesis, (2) knockdown experiments in Zebrafish and (3) knockdown of Shadoo, a protein with PrP-like functional domains, in PrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The restriction of the lentiviral infection to the trophoblastic cell lineage resulted in a similar lethal phenotype (Passet et al, 2012 ). Consistently, embryos invalidated for Prnp and/or knockdown for Sprn (Khalifé et al, 2011 ; Passet et al, 2013 ) display alterations of the expression of genes involved in placental angiogenesis, such as angiopoietin genes (Geva et al, 2005 ), cathepsins (Screen et al, 2008 ) and matrix metalloproteinases (Fontana et al, 2012 ). It would be of interest to assess in which extent, inactivation of Shadoo and co-inactivation with PrP affects Notch signaling in regards of PrP invalidation alone and consistently with the crucial role of this pathway for mouse placental fetal angiogenesis and proper trophoblast cell type specification (Gasperowicz and Otto, 2008 ).…”
Section: Co-invalidation Of Several Members Of the Prion Protein Genementioning
confidence: 89%
See 2 more Smart Citations
“…The restriction of the lentiviral infection to the trophoblastic cell lineage resulted in a similar lethal phenotype (Passet et al, 2012 ). Consistently, embryos invalidated for Prnp and/or knockdown for Sprn (Khalifé et al, 2011 ; Passet et al, 2013 ) display alterations of the expression of genes involved in placental angiogenesis, such as angiopoietin genes (Geva et al, 2005 ), cathepsins (Screen et al, 2008 ) and matrix metalloproteinases (Fontana et al, 2012 ). It would be of interest to assess in which extent, inactivation of Shadoo and co-inactivation with PrP affects Notch signaling in regards of PrP invalidation alone and consistently with the crucial role of this pathway for mouse placental fetal angiogenesis and proper trophoblast cell type specification (Gasperowicz and Otto, 2008 ).…”
Section: Co-invalidation Of Several Members Of the Prion Protein Genementioning
confidence: 89%
“…It remains that this RNAi strategy yielded seemingly contradictory result compared to the classical knockout approach. Several explanations were proposed to conciliate these observations (Daude and Westaway, 2012 ; Passet et al, 2013 ). It was suggested that the RNAi approach may induce a potential artifact resulting from either an off target effect of the two used shRNA only phenotypically visible in Prnp -knockout embryos or a toxicity associated with an shRNA over expression in single Prnp or double Prnp / Sprn knockout genotypes, linked to the role of PrP and potentially Shadoo in the regulation of the RISC complex (Gibbings et al, 2012 ).…”
Section: Co-invalidation Of Several Members Of the Prion Protein Genementioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent generation of viable Prnp −/− ; Sprn −/− animals is challenging this view (Daude et al, 2012 ). These apparently conflicting observations are discussed in Makhzami et al ( 2014 ).…”
Section: The Embryo Spills the Beansmentioning
confidence: 93%
“…For PrP, the quest for a gene/protein function has been particularly challenging because of the paucity of clear knockout phenotypes in mice (Steele et al, 2007 ). While this phenomenon may be explained by compensatory mechanisms (Málaga-Trillo and Sempou, 2009 ), the actual extent to which other genes can functionally replace PrP is only partly understood (Passet et al, 2013 ). More recent analyses of PrP knockout mice have revealed subtle defects in axon myelination and olfactory function as well as in the proliferation of neural precursors and self-renewal of hematopoietic stem cells (Steele et al, 2006 ; Zhang et al, 2006 ; Le Pichon et al, 2009 ; Bremer et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%